2016
DOI: 10.1051/0004-6361/201628353
|View full text |Cite
|
Sign up to set email alerts
|

Embedded star formation in the extended narrow line region of Centaurus A: Extreme mixing observed by MUSE

Abstract: We present a detailed study of the complex ionization structure in a small (∼250 pc) extended narrow line region (ENLR) cloud near Centaurus A using the Multi Unit Spectroscopic Explorer. This cloud is located in the so-called outer filament of ionized gas (about 15 kpc from the nucleus) where jet-induced star formation has been suggested to occur by different studies. We find that, despite the small size, a mixture of ionization mechanisms is operating, resulting in considerable complexity in the spatial ioni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…We find a similar situation in many blue compact dwarfs, which show recent clustered star formation even in very isolated locations after a long period of quiescence (Fuse et al 2012). We also mention the possibility of "jet-induced star formation" that has been discussed, for example to explain the existence of a young stellar population near Centaurus A at a galactocentric distance of 15 kpc (Mould et al 2000;Santoro et al 2016;Salomé et al 2016). In that case the age of SH2 would indicate the epoch of the last nuclear activity in NGC1316.…”
Section: Possible Formation and Evolution Of Sh2supporting
confidence: 77%
“…We find a similar situation in many blue compact dwarfs, which show recent clustered star formation even in very isolated locations after a long period of quiescence (Fuse et al 2012). We also mention the possibility of "jet-induced star formation" that has been discussed, for example to explain the existence of a young stellar population near Centaurus A at a galactocentric distance of 15 kpc (Mould et al 2000;Santoro et al 2016;Salomé et al 2016). In that case the age of SH2 would indicate the epoch of the last nuclear activity in NGC1316.…”
Section: Possible Formation and Evolution Of Sh2supporting
confidence: 77%
“…The structures covered by the MUSE field of views are mostly excited by energy injection from the radio jet or shocks. The small inclusion excited by star formation claimed by Santoro et al (2016) is spatially coincident with one CO structure.…”
Section: Excitation Of the Cloudsmentioning
confidence: 65%
“…a well-defined knotty filament and a more diffuse structure, as highlighted by optical excitation lines (VIMOS and MUSE;Santoro et al 2015a,b;Hamer et al 2015). Recently Santoro et al (2016) identified a star-forming cloud in the MUSE data that contains several HII regions. Some of these regions are currently forming stars, whereas star formation seems to have recently stopped in the others.…”
Section: Introductionmentioning
confidence: 99%
“…The MUSE data reveal three morphologically and kinematically distinct components in the ionised gas, which are thought to correspond to different stages in the jet-cloud interaction. The data also show that, overall, the ionisation of the gas is due to ionising photons from the AGN, but that locally star formation also plays a role (Santoro et al 2016). Interestingly, the rate at which the available gas reservoir is turned into stars is low, possibly connected to increased turbulence powered by injection Table 1) on the GALEX FUV image of the outer filament (Neff et al 2015).…”
Section: Special Region: the Outer Filamentmentioning
confidence: 79%